Acute abdomen as an unusual presentation of swine flu: Two case reports - Elbanna, Mohey Eldin R; Sharaf, Omar; Mahran, Mosatafa; Hammady, Walid (International Journal of Infection Control, 2011)
This report is about two cases of acute abdomen-like symptoms that proved to be due to swine flu. Two patients above 60 years of age, with cardiac and respiratory chronic disease, presented with acute abdominal pain. One of them was subjected to abdominal exploration that revealed functional colonic obstruction. The diagnosis of H1N1 was made later upon development of respiratory symptoms. In the other case the diagnosis of H1N1 was made preoperatively, and conservative management was pursued. Once H1N1 was suspected, viral culture was performed and found positive. Acute abdominal symptoms were relieved in both cases by administration of Oseltamivir. Acute abdomen-like presentation of H1N1 Influenza is rare. Suspecting such a diagnosis is crucial to save patients with an H1N1 Acute abdomen-like presentation unnecessary surgery. Cure of the patient and prevention of disease spread depend on accurate diagnosis of H1N1. Surgeons should be aware of the possibility of presentation with acute abdomen-like symptoms, during an H1N1 outbreak.